Clinical detection, diagnosis and treatment of morphological abnormalities of sperm flagella: A review of literature - Wang, Jiaxiong; Wang, Weizhuo; Shen, Liyan; Zheng, Aiyan; Meng, Qingxia; Li, Hong; Yang, Shenmin (Frontiers in Genetics, 2022)
Sperm is like a boat carrying the male genetic information, while the flagella are like the propellers. When the ultrastructure of the flagella is abnormal, the sperms are not able to reach the oocytes and achieve the insemination. Multiple morphological abnormalities of sperm flagella (MMAF), also termed as dysplasia of the fibrous sheath (DFS), is a relatively rare idiopathic condition that is mainly characterized by multiple defects in sperm flagella. In the last decade, with the development of genetic analysis approaches, lots of genes were revealed related with MMAF. However, we found there were always more or less differences in the sperm phenotypes and reproductive outcomes in so many cases, due to different pathogenic genes or different pathogenic loci in the same gene. Here, we will review information about the different phenotypes resulting from the difference pathogenic genes, including the sperm ultrastructure, the encoding proteins with their location and functions, and the assisted reproductive technology (ART) outcomes. We will share our clinical detection and diagnosis experience and try to provide more clinical views and broaden our understanding of this type of disease.